2024
DOI: 10.1021/acsomega.3c05982
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Photocatalytic-Dispersant System for Oil Spill Remediation

Selassie Gbogbo,
Emmanuel Nyankson,
Benjamin Agyei-Tuffour
et al.

Abstract: In the present work, the potential application of a fabricated halloysite nanotubes-Ag-TiO 2 (HNT-Ag-TiO 2 ) composite loaded with a binary surfactant mixture made up of lecithin and Tween 80 (LT80) in remediating oil spillages was examined. The as-prepared Ag-TiO 2 that was used in the fabrication of the HNT-Ag-TiO 2 -LT80 composite was characterized by X-ray diffraction, Raman spectroscopy, UV−vis and diffuse reflectance spectroscopy, CV analyses, and SEM-EDX. The synthesized composite was also characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 106 publications
(212 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the aerogel biodegrades within 30 days without causing environmental pollution [ 109 ]. Another potential application was examined by Gbogbo et al [ 110 ] when fabricating a halloysite nanotubes composite containing a binary surfactant mixture of lecithin and Tween 80, which was then exposed to UV light irradiation when in contact with crude oil. The results demonstrated that the composite was capable of photodegradation of the crude oil aromatics and asphaltene fractions, accompanied by the formation of intermediate photodegradation products, in accordance with the previously reported findings.…”
Section: Removing/containing Actionsmentioning
confidence: 99%
“…Furthermore, the aerogel biodegrades within 30 days without causing environmental pollution [ 109 ]. Another potential application was examined by Gbogbo et al [ 110 ] when fabricating a halloysite nanotubes composite containing a binary surfactant mixture of lecithin and Tween 80, which was then exposed to UV light irradiation when in contact with crude oil. The results demonstrated that the composite was capable of photodegradation of the crude oil aromatics and asphaltene fractions, accompanied by the formation of intermediate photodegradation products, in accordance with the previously reported findings.…”
Section: Removing/containing Actionsmentioning
confidence: 99%